2021
DOI: 10.1101/2021.03.04.21252853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in Cerebral Small Vessel Disease: a systematic review and meta-analysis

Abstract: Background: Cerebral small vessel disease (SVD) is an important cause of acute ischemic stroke and vascular dementia. Several studies recruiting more males than females have reported sex differences regarding SVD incidence and severity, but it is unclear whether this reflects underlying sex-specific mechanisms or recruitment bias. This work aimed to systematically review and meta-analyze potential sex differences in SVD by assessing the male-to-female ratio (M:F) of recruited participants and incidence of SVD,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This is in line with data already obtained in a limited sample of this cohort 14 as well as, more generally in sporadic small vessel diseases. 48 We also found that any previous history of hypertension was independently associated with the occurrence of stroke manifestations, dementia and dependency as already reported. 42,49 We confirmed in parallel that hypertensive patients had more lacunes and microbleeds as already detected.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with data already obtained in a limited sample of this cohort 14 as well as, more generally in sporadic small vessel diseases. 48 We also found that any previous history of hypertension was independently associated with the occurrence of stroke manifestations, dementia and dependency as already reported. 42,49 We confirmed in parallel that hypertensive patients had more lacunes and microbleeds as already detected.…”
Section: Discussionsupporting
confidence: 86%
“…Previous literature on sex differences in WMH is not extensive. [65][66][67] Sex hormones may play a role, as they show direct effects on the endothelium 68 and multiple brain cells, including oligodendrocytes producing myelin 69 and neurons. 70 In our study, female hormonal status was not likely a major factor in the observed sex specificities, as female participants were likely menopausal (average age >60 years).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was reported in a previous systematic review that reported a high male: female ratio in cohorts with higher SVD burden and among those with stroke. 62 While this may reflect recruitment bias seen in many hospital-based stroke treatment trials that include neuroimaging for cSVD, it may also imply that males develop higher cSVD severity, especially in stroke presentations which may, in turn, reflect male: female ratio differences in metabolomic. 63 Conversely, the male: female ratio did not predict cSVD prevalence in this meta-analysis, possibly due to the diluting effect of community-based studies in which cSVD prevalences are low.…”
Section: Discussionmentioning
confidence: 99%